1989
DOI: 10.1152/ajpregu.1989.257.1.r127
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ANP on circulating blood volume

Abstract: The effects of rat atrial natriuretic peptide (rANP) on blood volume (BV) were determined by the continuous measurement of BV, mean arterial pressure (MAP), and central venous pressure (CVP). Immediately after a single-bolus injection of rANP-(1-28), 1 nmol/100 g body wt, in conscious rats, BV began to decrease. Peak reduction of -0.22 +/- 0.03 ml/100 g body wt was reached 14.5 min after the injection. Thereafter, BV levels returned gradually to -0.08 +/- 0.03 ml/100 g body wt compared with the control value. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…According to previous studies [8,9] atrial natriuretic peptide (ANP) possibly increases capillary filtration coefficients. Zoccali et al [10] reported that plasma ANP concentration in diabetic uremics on chronic hemodialysis was increased due to autonomic failure, compared with nondiabetic uremics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to previous studies [8,9] atrial natriuretic peptide (ANP) possibly increases capillary filtration coefficients. Zoccali et al [10] reported that plasma ANP concentration in diabetic uremics on chronic hemodialysis was increased due to autonomic failure, compared with nondiabetic uremics.…”
Section: Discussionmentioning
confidence: 99%
“…month 9 Lp, ml/ mm Hg/ min 10 Vp0 liters 11 Lp/Vp0 Vp0/BW % 12 1 Cause of renal failure: 1 = diabetic nephropathy; 2 = nondiabetic nephropathy.…”
Section: Introductionmentioning
confidence: 99%
“…In anesthetized rats with bilateral liga tion of both the renal artery and vein, infusion of ANP induces reduction of blood volume and a 1.5-fold increase in the capillary filtration coefficient [10], Almeida et al [11] demonstrated that infusion of ANP for 40 min decreased the plasma volume by 14% in bilaterally nephrcctomized rats. They explained it as the result of efflux of fluid from capillaries.…”
Section: Discussionmentioning
confidence: 99%
“…It is not known how preload is reduced, since ANP does not appear to increase peripheral venous capacitance [26]. The reduction of pulmonary wedge pressure may reflect either an effect on the capillary permeability, with a transloca tion of fluid from the intravascular space to the interstitium, or a direct effect on the myo cardial diastolic relaxation [27]. Further, no significant changes in cardiac output, BP or systemic vascular resistance follows the re duction in preload.…”
Section: Atrial Natriuretic Peptidementioning
confidence: 99%